2021
DOI: 10.1126/sciadv.abc4897
|View full text |Cite
|
Sign up to set email alerts
|

Multiple screening approaches reveal HDAC6 as a novel regulator of glycolytic metabolism in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer without a targeted form of therapy. Unfortunately, up to 70% of patients with TNBC develop resistance to treatment. A known contributor to chemoresistance is dysfunctional mitochondrial apoptosis signaling. We set up a phenotypic small-molecule screen to reveal vulnerabilities in TNBC cells that were independent of mitochondrial apoptosis. Using a functional genetic approach, we identified that a “hit” compound, BAS-2, had a potentially similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Recently, a new interaction between the key redox metabolite NADPH and HDAC3 was discovered in adipocytes [64]. Novel high throughput functional genomics screening methods have identified HDAC6 as a regulator of glycolysis [65]. It is likely that there are several other metabolites like NADPH that may moonlight and play an epigenetic role.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new interaction between the key redox metabolite NADPH and HDAC3 was discovered in adipocytes [64]. Novel high throughput functional genomics screening methods have identified HDAC6 as a regulator of glycolysis [65]. It is likely that there are several other metabolites like NADPH that may moonlight and play an epigenetic role.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the acetyl group induces oligomerization and activation of GLS which reduces oxidative stress in cancer cells therefore promoting their survival 70 . Glycolytic enzymes have been proposed to be substrates of HDAC6 71 , and our acetylome screen identified two glycolytic enzymes shown to interact with HDAC6, phosphoglycerate kinase 1 (PGK1) 72 and pyruvate kinase muscle (PKM) 73 . The acetylome screen identified additional metabolic enzymes, including heme oxygenase 1 (HMOX1) 74 , ATP-citrate lyase (ACLY) 56 , and malic enzyme 1 (ME1) 75 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the second-phase clinical study show that FK228 can effectively control T-cell lymphoma, with safety and reliability (NCT00426764, NCT00106431) (Table 2) (Foss et al, 2014;Foss et al, 2016). The HDAC inhibitor BAS-2 inhibits HDAC6, affects the ENO1 gene and LDHA related to glucose metabolism, and ultimately affects glycolysis in breast cancer (Dowling et al, 2021). Studies have shown that 1A12 can inhibit the acetylation level of histone H3, and it can also affect the glucose metabolism level in preclinical test subjects (Chan et al, 2014).…”
Section: Clinical Trialsmentioning
confidence: 99%